Analysis of Odds Ratio for Employment Status Risen Migration - dilla; kukuh (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
Migration in Indonesia continues to increase, with the majority of migrants moving in pursuit of more decent employment. This study aims to examine the characteristics and determinants of risen migration in the labour market, distinguishing between workers in the formal and informal sectors, using binary logistic regression analysis based on microdata from the August 2023 National Labour Force Survey (SAKERNAS). The analysis focuses on the employment status formal or informal sector of risen migration as the dependent variable. The research coverage spans all 34 provinces and 514 regencies/cities in Indonesia. The definition of a 'risen migration' follows the SAKERNAS classification: an individual whose current residence differs from their place of residence five years prior, in 2018. Data analysis was conducted using quantitative methods, incorporating both descriptive and inferential approaches through binary logistic regression. The results indicate that all independent variables namely respondent age, gender, marital status, education, vocational training, income, and work experience exert a significant influence, both negative and positive, on labour mobility decisions. Specifically, workers with higher educational attainment, those of males, income and work experience are predominantly represented in the formal sector. Conversely, marital status and non-productive age are associated with employment in the informal sector.